PENGARUH LIKUIDITAS, EFEKTIVITAS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN: (Studi Pada Perusahaan Sub Sektor Makanan dan Minuman Yang Terdaftar di Pasar Modal Indonesia) - Divanis Vivinia; Ruslan Somad; Iing Sri Hardiningrum; Lulud Wijayanti (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This research aims to determine and analyse whether the liquidity, effectiveness, and size of the company affect the devidend policy on the food and beverage Sub-sector manufacturing company registered in the Indonesian capital market Period from 2013 to 2017 both simultaneously and partially. The population of this study amounted to 18 companies. By using purposive sampling technique, obtained as many as 6 companies as samples. Data collection is done by documentation techniques, library studies, and web searching. Financial report Data is obtained through the official website www.idx.co.id. The data analysis techniques used are using multiple linear regression analysis techniques. The test results showed that the company's liquidity, effectiveness, and size were significantly influential on the dividend policy. Partial liquidity and effectiveness has no significant effect on the devidend policy, while the company's partial size has significant effect on the devidend policy. The adjusted value of R Square (adjusted R2) in this study amounted to 0.182, this means that 18.2% of the dividend policy variation can be explained by the liquidity, effectiveness, and size of the company. The remaining 81.8% is explained by other factors that can affect the dividend policy.